CODE MIXING IN ISLAMIC LECTURES BY USTADZ EVIE EFFENDI - Triana, Asep; Eka Saputra, Siddik Sembada (PROJECT (Professional Journal of English Education), 2018)
This study is aimed to find the kinds of code mixing and to know which kinds of code mixing are dominantly used in Islamic lectures by Ustadz Evie Effendi. Descriptive qualitative method is used in this study. The data were collected through watching, transferring, asking, playing, selecting and transcribing the data from the lectures. The collected data were then analyzed through identifying the data, selecting the data related to the code mixing, listing and classifying the data based on the kinds of code mixing and finally drawing conclusion. It was found that there are two kinds of code mixing used by Ustadz Evie Effendi, namely conversational and situational code mixing. Between two kinds of code mixing, conversational code mixing is dominantly used both by Ustadz Evie Effendi in which he sometimes change the pronunciation from English into Indonesian in the conversation.